Inhibitory effects of aspirin-triggered resolvin D1 on spinal nociceptive processing in rat pain models - Meesawatsom, Pongsatorn (J Neuroinflammation, 2016)
BACKGROUND: Harnessing the actions of the resolvin pathways has the potential for the treatment of a wide range of conditions associated with overt inflammatory signalling. Aspirin-triggered resolvin D1 (AT-RvD1) has robust analgesic effects in behavioural models of pain; however, the potential underlying spinal neurophysiological mechanisms contributing to these inhibitory effects in vivo are yet to be determined. This study investigated the acute effects of spinal AT-RvD1 on evoked responses of spinal neurones in vivo in a model of acute inflammatory pain and chronic osteoarthritic (OA) pain and the relevance of alterations in spinal gene expression to these neurophysiological effects. METHODS: Pain behaviour was assessed in rats with established carrageenan-induced inflammatory or monosodium iodoacetate (MIA)-induced OA pain, and changes in spinal gene expression of resolvin receptors and relevant enzymatic pathways were examined. At timepoints of established pain behaviour, responses of deep dorsal horn wide dynamic range (WDR) neurones to transcutaneous electrical stimulation of the hind paw were recorded pre- and post direct spinal administration of AT-RvD1 (15 and 150 ng/50 μl). RESULTS: AT-RvD1 (15 ng/50 μl) significantly inhibited WDR neurone responses to electrical stimuli at C- (29 % inhibition) and Aδ-fibre (27 % inhibition) intensities. Both wind-up (53 %) and post-discharge (46 %) responses of WDR neurones in carrageenan-treated animals were significantly inhibited by AT-RvD1, compared to pre-drug response (p < 0.05). These effects were abolished by spinal pre-administration of a formyl peptide receptor 2 (FPR2/ALX) antagonist, butoxy carbonyl-Phe-Leu-Phe-Leu-Phe (BOC-2) (50 μg/50 μl). AT-RvD1 did not alter evoked WDR neurone responses in non-inflamed or MIA-treated rats. Electrophysiological effects in carrageenan-inflamed rats were accompanied by a significant increase in messenger RNA (mRNA) for chemerin (ChemR23) receptor and 5-lipoxygenase-activating protein (FLAP) and a decrease in 15-lipoxygenase (15-LOX) mRNA in the ipsilateral spinal cord of the carrageenan group, compared to controls. CONCLUSIONS: Our data suggest that peripheral inflammation-mediated changes in spinal FLAP expression may contribute to the novel inhibitory effects of spinal AT-RvD1 on WDR neuronal excitability, which are mediated by FPR2/ALX receptors. Inflammatory-driven changes in this pathway may offer novel targets for inflammatory pain treatment. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12974-016-0676-6) contains supplementary material, which is available to authorized users.